Factors affecting the profitability of pharmacies - Pampel, Graham (My University, 2014)
In South Africa, the pharmaceutical industry has been in a state of flux since the end of apartheid. The Department of Health intends to make healthcare available to all and, in so doing, a number of laws have changed. These laws have affected the entire medicine supply chain and have caused the cost of medicine to be reduced in order to make it more affordable. However, this price fixing or ceiling, as implemented by the Department of Health, has resulted in a number of pharmacy closures. This research paper thus attempts to identify factors which affect the profitability of pharmacies so that pharmacies can devote their time and efforts to areas that will result in the best outcomes. In this research, the factors identified and tested included average inventory holding, floor space, product mix and location. Other ancillary variables were also tested, including customer loyalty, advertising, prescribing and buying patterns, buyer groups and the effect of information technology. In testing the location, an index was developed from four other factors, which added a level of complexity to the variable that is also apparent in the retail literature. The method used to analyse these factors was least squares regression. Data was obtained from a questionnaire completed by a sample of 65 pharmacies situated in Johannesburg, South Africa. Cluster analysis also provided insight into the location factor. The results of this research prove that average inventory holding and floor space have an effect on the profitability of pharmacies. However, location and product mix appear to have no relationship with pharmacy profitability. A number of interesting conclusions were drawn, for example customer loyalty and the number of doctors near the pharmacy seem to have some relationship with pharmacy profitability. Other factors not examined by this research could be considered in the future to determine their relationship with profit.